Myiasis in Percutaneous Transhepatic Biliary Drainage Site - Tripathy, Tara Prasad; Patel, Ranjan; Debbarma, Ripan; Gupta, Sunita; Pattanaik, Brahmadutta (Journal of Clinical Interventional Radiology ISVIR, 2024)
The infection of dipterous larvae causes myiasis. It is generally associated with unsanitary conditions. An interventional radiologist rarely comes across myiasis. We report a case of myiasis around a percutaneous transhepatic biliary drainage (PTBD) tube. A 31-year-old man from a rural area underwent left PTBD for cholangiocarcinoma and was discharged with an internal–external drain. Two weeks later, he presented with pain in the local site, pruritus, and bile leakage. He was found to have maggots around the PTBD tube with poor wound hygiene. Treatment included turpentine oil instillation and oral and topical ivermectin, accompanied by manual removal of the larva.
Keywords: myiasis; percutaneous transhepatic biliary drainage; ivermectin